A review of integration between BIM and CFD for building outdoor environment simulation - Zheng, Lang; Lu, Weisheng; Wu, Liupengfei; Zhou, Qianyun (Building and environment, 2023)
Numerous studies have demonstrated that the climate of cities and human settlements can affect building performance and human comfort. Historically, ambient data were collected through on-site measurements or simulations using physical models. Nowadays, with the advancement of data-based techniques and computing resources, especially Building Information Modeling (BIM) used to address the requirement for building data and numerical simulation with Computational Fluid Dynamics (CFD) used to assess building outdoor environments have increased in popularity. This paper presents a review of publications on this topic till 2022. The reviewed publications are categorized into different sections according to the following characteristics: general BIM-CFD integration process, building design optimization, and integration process optimization. In addition, the reviewed publications are categorized by the BIM design parameters, CFD simulation equations, building locations, BIM software, and BIM-CFD integration approach under consideration. This review discusses current research trends and major research issues in detail and presents future perspectives. The results show that from the early to late stages of the BIM-CFD integrated environmental studies, the BIM parameters considered were shifted from 3D to nD (e.g., energy). Meanwhile, CFD models and new technologies were chosen more carefully to meet the needs of different building scenario simulations. Although the current dynamic data transfer and synchronization capabilities between BIM and CFD need to be improved and rely heavily on the development of efficient Application Programming Interfaces (API), both BIM and CFD still play an indispensable role in building design practice. •Application of BIM-CFD integration approach in building outdoor environment simulation is reviewed.•The BIM parameters that influence the modification of the climate in the building external space are outlined.•The detailed data exchange processes in the various BIM-CFD integration approach are outlined.•Potential use of BIM-CFD integration approach to building outdoor environment simulation is discussed.